Evaluating YouTube Video Quality in Orthognathic Surgery Patient Education. Issue 1 (March 2022) - Puthumana, Joseph S.; Lopez, Christopher D.; Girard, Alisa; Lake, Isabel V.; Taylor, Ainsley L.; Khoo, Kimberly H.; Rottgers, Alex; Yang, Robin; Halsey, Jordan
Background: Patients are increasingly accessing consumer-style health information from a variety of web-based platforms. This study aims to assess a popular audio-visual platform for its quality of information in orthognathic procedures.Methods: We queried YouTube on August 12th, 2021 for 20 videos, by both relevance and view count, under each of 3 search terms: (1) "orthognathic surgery, " (2) "LeFort I osteotomy, " and (3) "sagittal split osteotomy." Each video was characterized by date of upload, time since upload, video duration, video type, and video author. Videos were further characterized by type of video (1) creator and (2) category. The provider-validated instrument DISCERN was applied to each video to assess content quality and bias.Results: Of 60 videos marked for review, 46 were included for analysis. The most common category of video was operative ( n  = 18, 36.1%), while the most common creator type was non-physician medical professional ( n  = 14, 30.4%). Hospital or physician advertisement videos had the greatest video power index (26 297 ± 44 556), while medical education videos had the least (13 ± 9). Significant differences were found across both video type and video creator in viewership ( P  = .008 and .003, respectively) and video power index ( P  = .010 and .007), but not duration ( P  = .796 and .059). DISCERN scores ranged from 16 to 80 and were subdivided into 5 categories: very poor (16-28), poor (29-41), fair (42-54), good (55-67), and excellent (68-80). Average DISCERN scores for all 46 videos were 17.9 ± 4.9 for reliability, 14.2 ± 4.0 for quality, and 34.3 ± 9.0 for overall.Conclusions: YouTube videos on orthognathic surgery were of overall poor quality. These videos were rated best in relevance to the search parameter and description of treatment but were least helpful in describing alternatives to the treatment and uncertainties about the procedure. Videos created by patients and about patient experiences were rated best for content that was reliable, high quality, and low bias.